Pengaruh Populasi, Jumlah Pemotongan, Hasil Produksi Ternak terhadap Produk Domestik Bruto (PDB), dan Penanaman Modal Dalam Negeri (PMDN): Pengaruh Populasi, Jumlah Pemotongan, Hasil Produksi Ternak terhadap Produk Domestik Bruto (PDB), dan Penanaman Modal Dalam Negeri (PMDN) - Hartati, Hartati; Prakasa, Awal Indut; Kholis, Nur; Hilmi, Ihsan (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: Sustainable livestock development is a major factor in livestock development. Livestock business development is directly related to the livestock population in Indonesia. The livestock population must be able to be a success factor for livestock development. Animal husbandry must be able to produce superior livestock populations and increase income. Livestock population is closely related to investment, meaning that the potential and opportunities can provide added value to the livestock business. Livestock investment in Indonesia over the past few years has increased significantly. The proof of this is the increase based on the 2023 Animal Husbandry and Animal Health Statistics data, namely the Livestock GDP in 2022 of IDR178.1 trillion (at constant prices) or an increase of 6.24% from 2021. Livestock GDP of Rp298.0 trillion (at current prices), contributed 16.51% to the GDP of the Agricultural Sector. Meanwhile, the result of the realisation of DCI investment in Animal Husbandry in 2022 was RpR3.9 trillion or an increase of 82.74% (an increase compared to 2021). The livestock sub-sector has a positive effect on increasing the value of GDP, GRDP, and DCI in Indonesia. This means that the value of GDP and DCI is also influenced by the value of the contribution of the livestock sub-sector in Indonesia. The challenge of the livestock sub-sector is to be able to meet the needs of larger livestock resources and the expansion of infrastructure in the livestock sector. There is an influence of the relationship between sustainable livestock development and the number of livestock populations. If the livestock population is high, it can increase the productivity of livestock. Reviews: This paper will briefly review the livestock sub-sector, namely the Effect of Population, Total Slaughter, Livestock Production on Gross Domestic Product (GDP), and Domestic Capital Investment (DCI).